Reshaping Emergency Care: Dynamics of OHCA and STEMI in a Three-Year Analysis - Francesca Bottega; Erika Kacerik; Gabriele Perotti; Carlo Signorelli; Giuseppe Ristagno (MDPI AG, 2024)
The COVID-19 pandemic drastically reshaped healthcare in Lombardy, Italy, notably impacting EMS and emergency departments and altering the epidemiology of time-dependent pathologies such as STEMI and OHCA. While previous studies focused on modifications during the pandemic peak, with an increase in the number of OHCA diagnoses and a reduction in the number of STEMI, little evidence exists regarding the inter-pandemic phases. We analyzed OHCA and STEMI accesses to the ED in the regional emergency department access register (EUOL) for 2019-2021. The analysis revealed a significant difference in monthly diagnosis averages. For STEMI, the change was statistically significant (F(2, 33) = 4.45, p = 0.02), while it was not for OHCA (F(2, 33) = 0.18, p = 0.83). Despite the monthly decreases, the likelihood of receiving a STEMI diagnosis increased with total accesses, OR 1.40 [95% CI 1.25-1.58, p < 0.0001]. Additionally, there was a significant increase in March 2020 discharge diagnoses for OHCA compared to March 2019, OR 3.35 [95% CI 2.88-3.90, p < 0.0001], corresponding to the first pandemic wave. Therefore, our analysis indicates that the epidemiology of STEMI and OHCA was altered during the COVID-19 pandemic.